Paradox Of Identities, Girls As Wives, Boys As Children: The Attitude Of In-School Female Adolescents In Enugu State Towards Early Marriages In Nigeria. - Nnabueze, Ursula Chigozie (Advances in Social Sciences Research Journal, 2019)
Adolescence is a critical transitional period of physical, emotional and psychological changes. It is a very critical period of self-identity formation, but some traditional/cultural practices complicate and confuse the girl child as to who she really is. Is she a girl child or a woman already? This leads to the perception of a girl today, a woman the next day because the girl child could be married off within the blink of an eye. Early marriage, also known as child/forced marriage, is among the Harmful Traditional Practices (HTPs) still perpetrated in some parts of Nigeria today. HTPs are forms of violence which are committed primarily against girls and women in certain communities for so long that they are considered or presented by perpetrators as part of acceptable cultural practices — the most common being forced/early marriage. Popular discussions tend to focus attention on early marriage in Muslim communities of Northern Nigeria. However, some studies have reported that early marriage also occurs in some Muslim (Western) and Christian (Eastern) communities of Southern Nigeria. Ironically, boys are treated as boys while girls are treated as marriageable women. A cross sectional survey research design was adopted for the study. The population comprised of 27,831 female secondary school students from the all-girls 35 secondary schools in Enugu Education Zone, Enugu state, Nigeria. The multi-stage sampling procedure was adopted to select the sample size of 320 girls from four schools. The instrument for data collection was a structured questionnaire titled Attitude of Adolescents toward Early Marriages (AATEM). The questionnaire was validated by three experts and a reliability index of. 81 was obtained. Data analysis performed using simple percentages showed that a great percentage of these girls have negative attitude towards early marriages. The study recommended that government and other social institutions must guarantee girls’ access to basic education and find new ways to enable families enroll girls in school, encourage them to stay in school, and thereby delay premature marriages.